Dampak Penggunaan Bahasa Daerah Terhadap Bahasa Indonesia di Lingkungan Pendidikan, Khususnya di Universitas Negeri Medan - Surip Muhammad; Tulus Marco Diaztro Nainggolan; Michael Hutagaol; Fajar Ferdian Telaumbanua (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The use of regional languages ​​in educational environments has a significant impact on the use of Indonesian. The findings show that the use of regional languages ​​can influence Indonesian language skills, especially in academic contexts. In addition, the use of regional languages ​​can also create communication gaps between individuals from different linguistic backgrounds. The implication of this research is the need for an approach strategy that combines the use of regional languages ​​with strengthening the use of Indonesian as an official language in the educational environment. This research aims to determine the use of regional languages ​​towards Indonesian, especially in the educational environment, as well as to determine and analyze measures to prevent the occurrence of mixed languages ​​(regional languages ​​and Indonesian). This research was conducted in an educational environment, especially at Medan State University. Through a quantitative research approach, data is collected through questionnaires that are direct comparisons between teenagers who often use regional languages ​​and Indonesian simultaneously.